2022
DOI: 10.1186/s13098-022-00939-1
|View full text |Cite
|
Sign up to set email alerts
|

Overt diabetes imposes a comparable burden on outcomes as pregestational diabetes: a cohort study

Abstract: Background Women with diabetes first diagnosed during pregnancy (overt diabetes) may be at the same risk level of adverse outcomes as those with known pregestational diabetes. We compared pregnancy outcomes between these groups. Methods We evaluated pregnant women with type 2 diabetes, pregestational or overt diabetes, attending high risk antenatal care in two public hospitals in Southern Brazil, from May 20, 2005 to June 30, 2021. Outcomes were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This finding can be explained by the worse glycemic control observed in overt pregnant women and by the fact that none of these women planned their pregnancy. In a case-control study that has evaluated 414 women with T2DM and 204 women with ODM, no differences in maternal and fetal outcomes have been found when also considering congenital malformations; this study underlines that the mean values of HbA1c at the initial appointment were no different and no worse in the two groups (7.2 vs. 7.4%), and 70% of the women were white [17]. It was observed in this study that 52.5% of women with ODM went to a specialized prenatal care center in the third trimester of pregnancy, while those with T2DM went during the first trimester.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This finding can be explained by the worse glycemic control observed in overt pregnant women and by the fact that none of these women planned their pregnancy. In a case-control study that has evaluated 414 women with T2DM and 204 women with ODM, no differences in maternal and fetal outcomes have been found when also considering congenital malformations; this study underlines that the mean values of HbA1c at the initial appointment were no different and no worse in the two groups (7.2 vs. 7.4%), and 70% of the women were white [17]. It was observed in this study that 52.5% of women with ODM went to a specialized prenatal care center in the third trimester of pregnancy, while those with T2DM went during the first trimester.…”
Section: Discussionmentioning
confidence: 66%
“…Due to the similar physiopathology of overt diabetes and pre-existing type 2 diabetes, women with overt diabetes may be at the same risk of adverse outcomes as those with known pre-existing diabetes, but data reported in the literature are scarce and conflicting. In particular, Oppermann et al have shown that there are no differences in pregnancy outcomes in the two groups of evaluated pregnant women [17]. Significant differences in macrosomia and neonatal jaundice are reported by Schiller et al: this study compared pregnant women with prediabetes and pregnant women with pregestational overt type 2 diabetes, which included women with known type 2 diabetes or those that are first diagnosed during pregnancy [18].…”
Section: Introductionmentioning
confidence: 87%
“…This finding can be explained by the worse glycemic control observed in overt type 2 pregnant women and by the fact that none of these women planned their pregnancy. In a case control study that has evaluated 414 T2DM and 2014 OT2DM even if women with OT2 DM arrived to specialized prenatal care center at the third trimester of pregnancy while those with T2DM at the first trimester no differences in maternal and fetal outcomes have been found also considering congenital malformations; it is to notice that mean values of HbA1c at booking were no different and no bad in the two groups ( 7.2 vs 7.4 %),and that 70% of women were white (15).In a retrospective study comparing 120 OT2DM pregnant women and 86 T2DM, 75% of caucasian race, even if 55% of OT2DM women arrived late at the specialized prenatal care center no significant differences have been found in the two groups regarding maternal an fetal outcomes (16). It is to notice however that OT2 DM have significantly lower values of HbA1c compared to T2DM in pre pregnancy and in the first trimester and that no data are reported on congenital malformations.…”
Section: Discussionmentioning
confidence: 98%
“…Diabetes is one of the major causes of stillbirths worldwide. A significant correlation exists between the metabolic control of the mother during pregnancy and the adverse outcomes for hyperglycemic pregnancies ( 55 ). Uncontrolled diabetes in early gestation, especially if present in the first few weeks, adversely impacts placental growth and development and predispose to intra-uterine growth restriction ( 56 58 ).…”
Section: Discussionmentioning
confidence: 99%